The consequences of dual and unilateral commitment to the organisation and union. (28th January 2016) - Redman, Tom; Snape, Ed
Abstract : This article examines the pattern and consequences of commitment to organisation and union amongst union members in a UK National Health Service Trust. Those who perceived the industrial relations climate as positive were more likely to be dually committed to both organisation and union. As anticipated, union commitment predicted union citizenship behaviours and intent to quit the union. However, organisational commitment predicted intent to quit the organisation but not organisational citizenship behaviour, which was predicted by union commitment. Findings suggest that those with a unilateral commitment to the union are more likely than the dually committed to engage in citizenship behaviours aimed at helping fellow members and colleagues, perhaps because they feel unconstrained by any strong loyalty to the organisation.